Blocking entry of hepatitis B and D viruses to hepatocytes as a novel immunotherapy for treating chronic infections - Maravelia, Panagiota; Frelin, Lars; Ni, Yi; Caro Pérez, Noelia; Ahlén, Gustaf; Jagya, Neetu; Verch, Georg; Verhoye, Lieven; Pater, Lena; Johansson, Magnus; Pasetto, Anna; Meuleman, Philip; et al. (The journal of infectious diseases, 2021)
The paper shows a completely new immunotherapy for chronic hepatitis B and potentially also hepatitis D. The immunotherapy induced neutralizing antibodies and T
Published online January 29, 2020
Gesehen am 26.02.2021